The Role Of Financial Technology In Increasing Islamic Financial Inclusion: Analysis Of Potential And Challenges - Ceta Indra Lesmana; Lestari Budianto (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to find out the role of financial technology in increasing Islamic financial inclusion. The method used in this research is a descriptive qualitative method with a type of literature study research obtained from sources related to research, such as books, journals and websites which are processed into research material. The research results show that the potential and challenges of financial technology can increase Islamic financial inclusion, where there are various financial technologies that have the potential to improve finances: first, Mobile Banking and Financial Applications. Second, Sharia Payment Gateways. Third, Peer-to-Peer Lending. Fourth, Sharia Crowdfunding. Fifth, Blockchain and Smart Contracts. Apart from that, the challenges in increasing Islamic financial inclusion are: first, awareness and education. Second, supporting regulations. Third, Technology and Infrastructure. Fourth, security and data protection.